COUROUPITA GUIANENSIS LEAF CALLUS EXTRACT MEDIATED SYNTHESIS AND ANTIBACTERIAL ACTIVITY OF SILVER NANOPARTICLES. - VENKATA RAJESH KUMAR T; NARAYANA RAO MADAMSETTI; Y, Bhargava; Murthy Jsr (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Synthesis of varied sized and morphologically distinct silver nanoparticles (AgNPs) using callus/callus extract, and their promising antibacterial and cytotoxicity was reported from very few plant systems. Here, we investigated silver nanoparticle synthetic potential of Couroupita guianensis leaf callus extract and their antibacterial activity. Methods: synthesis of callus mediated silver nanoparticles and characterisation of physical, chemical, and antibacterial activity of AgNPs. Results: Callus extract rapidly reduced silver ions and stabilized nanoparticles have displayed characteristic maximum UV absorbance at 410 nm. SEM and AFM images revealed their spherical morphology and size variation, which is ranged from 30.38 nm to 88.32 nm and were in small aggregates. Capping of AgNPs by the phenolic compounds and proteins revealed from FTIR spectral peaks. Silver nanoparticles displayed significantly high antimicrobial activity against both Gram positive and negative bacterial strains compared to silver ions and gentamicin. This enhanced antimicrobial activity of AgNPs may due their small size leading to efficient molecular contact with cell surface, and uptake and interaction with vital biomolecules. Conclusions: Stable AgNPs were synthesized through reduction and capping of silver ions by polyphenols and proteins present in callus extract. The enhanced antimicrobial activity of AgNPs may due to their small size leading to efficient molecular contact with the cell surface, penetration, and interaction, and inactivation of vital biomolecules. Â